Can you drink money?: integrating organizational perspective-taking and organizational resilience in a multi-level systems framework for sustainability leadership - Tuazon, Gerson Francis (Journal of business ethics, 2021)
Social and environmental shocks associated with freshwater management are inherently tied with the lives and well-being of all global citizens. Thus, exploring key actors’ roles is a critical element of this grand challenge. Utilizing an inductive multiple case study, we explore sustainability leadership and subsequent organizational perspective-taking behaviours initiated by actors within freshwater management in response to the grand challenge. A vibrant inductive model elicited three main themes: (1) identifying conditions for organizational perspective-taking, (2) modifying organizational frames of reference and (3) emergence of multi-level influence. The discussion extracts critical insights for sustainability leadership and highlights complexities involved in facilitating effective decision-making among diverse actors. Fundamentally, this article contributes a distinct multi-level systems framework for sustainability leadership drawing from social-ecological systems theory and organizational resilience. We conclude by offering future research opportunities within sustainability leadership designed to bridge the gap between grand challenges and our abilities to solve them.